Transforming UV‐Curable Emulsions for Arbitrary Patterning: A 2‐Layer Approach without Line‐and‐Space Constraints - Yoshimi Inaba; Yasunori Kurauchi; Takayuki Yanagisawa (Macromolecular Materials and Engineering)
Abstract The development of on‐demand patterning technology aims to replace traditional methods such as embossing, photoetching, and screen printing, offering an efficient process with low environmental impact and high industrial value. By directly exposing an oil‐in‐water (O/W) UV‐curable emulsion liquid film to a UV light pattern and then drying the film, large‐pitch‐and‐depth uneven (concave–convex) patterns can form in a self‐organizing manner. This method utilizes the aggregation of cured emulsion in the liquid film and the coalescence of uncured droplets in unexposed areas during drying. The coalesced oligomer droplets penetrate the voids in the cured‐particle pattern layer, creating an uneven structure. However, when the line‐and‐space (L/S) ratio is 1/1 or larger, the density of voids in the pattern film increases, and when it is <1/1, the pattern edges lose sharpness, limiting the method to repetitive patterns. In this study, a 2‐layer emulsion film: the lower layer absorbs the coalesced oligomer droplets from unexposed areas, and the upper layer forms a cured‐particle aggregation pattern is proposed. This approach allows arbitrary patterning without L/S constraints and produces no waste other than dried water. An example of arbitrary pattern formation with a depth of ≈0.3 to 0.4 mm is demonstrated.